CSR communication and firms' ability to win public procurement contracts - Ouiam Kaddouri; Stéphane Saussier (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - This paper aims to examine the link between the corporate social responsibility (CSR) communication efforts of companies and their ability to obtain public procurement contracts. Design/methodology/approach - The authors are exploiting a database with the number of public procurement contracts won by SBF 120 companies in France and a constructed CSR index over the period of 2007-2015. The authors provide estimates of the amount of public contracts won by those companies. Findings - The results suggest a striking influence of CSR communication on the ability of firms to win contracts. Research limitations/implications - This study focused on the case of the SBF 120 companies under the French regulatory system and European directives, which are different from the obligations in North American countries. Second, our constructed CSR index may be too simplistic in nature, and its application is limited only to the French context. Third, we do not have any evidence about the efficiency of well-ranked firms in our study. CSR reporting is still considered to be a form of communication, even if formal, that can contain information that does not especially reflect reality, as the scandals of several companies have shown in recent years (e.g. Volkswagen, Eiffage, Enron). Practical implications - Companies should consider Business-to-Government (B-to-G) market when investing in CSR actions. Originality/value - This is one of the first empirical studies measuring the impact of CSR on the ability of companies to win public contracts.
Keywords: H57; L33; 650; Asymmetric information; CSR communication; CSR index; Public procurement; Responsible public procurement